Sposób na czytelników, czyli promocja czytelnictwa w Pedagogicznej Bibliotece Wojewódzkiej im. Mariana Rejewskiego w Bydgoszczy .......... 105 - Pronobis-Sosnowska, Ewa (Skąd się biorą czytelnicy?, 2025)
THE TRICK TO GAIN READERS, OR THE PROMOTION OF READING IN THE MARIAN REJEWSKI PROVINCIAL PEDAGOGICAL LIBRARY IN BYDGOSZCZThe article is meant for librarians and teachers who make diverse wholehearted efforts to promote reading in order to increase the number of users of pedagogical libraries. It presents educational projects and original programs developed by librarians and teachers and carried out in the Marian Rejewski Provincial Pedagogical Library in Bydgoszcz in order to promote the institution and encourage more readers to use its resources. All activities described aim at showing the most effective ways of promoting reading in terms of gaining more library users.